Measuring Thriving Experience in Physical Working Spaces - Fathy, Yasmin; Pärn, Erika A.; Wilkins, Denise; Zaki, Mohamed (2020)
ABSTRACT The global pandemic has enforced corporations to shift into new working patterns and design upgrades of the physical working space - from packed desks to long-term modifications design, putting well-being at the heart of workplace planning. This paper hypothesises the use of technologies to revolutionise work practices for monitoring the well-being in a physical space. New human-computer interaction approaches can be introduced to measure psychophysical and physical metrics to gauge occupant thriving in indoor office environments. They offer changes to the working environment, e.g. breaks and lighting to enhance productivity and well-being. This research investigates three domains to measure human thriving indoor: (a) methods used in architecture domain to understand the impact of architecture design on human thriving, (b) current approaches in the sensory domain to evaluate human physiological and psychological states, and (c) non-obtrusive methods of psychophysical data collection. Keywords physical spaces; health and well-being; video-based physiological measurement; emotional responses; psychophysiological measurement; emotional intelligence; deep learning ABOUT THE AUTHOR/S Yasmin Fathy University of Cambridge yafa2@cam.ac.uk Yasmin Fathy is a Research Associate in IoT and Machine Learning at the University of Cambridge. Before joining Cambridge, she was KTP Research Associate in Data Science and Machine Learning at UCL, Computer Science department. She obtained her PhD in Electrical and Electronic Engineering from the Institute for Communication Systems (ICS) at the University of Surrey and MSc in Applied Science and Engineering from Vrije Universiteit Brussel (VUB) in Belgium. Erika A. Pärn University of Cambridge eap47@cam.ac.uk Dr. Erika A. Pärn [PhD, BSc (Hons), PgCE, PgCR] is a Research Associate at University of Cambridge supporting the IfM and CDBB. Previously whilst working in industry, she led multiple research project technical deliverables for the EU commission on two H2020 initiatives and secured a KTP research grant to automate and digitize manufacturing with BIM. E.A. Pärn was employed as an Architectural Technology Lecturer at Birmingham City University in 2014 and commenced her PhD studies in 2016. Her PhD has focused upon BIM enabled FM to automate decision support for facilities management teams seeking to reap the inherent benefits of geometric and semantic data for operations and maintenance and evaluated the use of BIM and cloud-based technologies to streamline facilities management into the as-built BIM via three case studies at Birmingham City University. Erika’s research investigations have thus far included: BIM and FM integration; design development automation; clash detection; laser-scanning; engineering design; construction management in developing countries; built environment cyber-security; and networked and sensor-based BIM integration. Denise J. Wilkins Microsoft Research, University of Cambridge t-dewilk@microsoft.com Mohamed Zaki University of Cambridge mehyz2@cam.ac.uk New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s)